Legal Implications Of Water Supply Management in Batam City (Post Issuence of Indonesia’S Court of Constitution Decree No. 85/PUU – XI/2013) - saputra tanwir, yopta eka; Situmeang, Ampuan; Sudirman, Lu (Universitas Internasional Batam, 2024)
Indonesia’s Court of Constitution has issued decree No. 85/PUU-XI/2013, which annuls the Law No. 7 Year 2004 governing water resources. It has implicated the state’s acquisitions over the water resources in particular and in general other resources of natural productions of the common basic need of entire people in the country (as stated in the Indonesia’s constitution in Article 3 of Chapter 33). In Batam city water resources has been administered by PT Adhya Tirta Batam (ATB) for 25 years as an exclusive holder of full concession for sites of water resources. Afterward it carried on by PT Moya Indonesia that was appointed through a scheme of government – private parties cooperation (KPBU) between the Administrative Body of Batam (BP Batam) and the company for another 15 years. The BP Batam then established PT Air Batam Hulu and PT Air Batam Hilir, which violates Batam residents’ constitutional right and human right for water. This research is committed with methods of normative jurisdiction – and so the research outputs will eventually show norms that are recognized by the law. We seek truths through reconstructions of law enforcements over BP Batam’s failures of water management in Batam city. Citizen law suits is one out of some options chosen for legal protection of residents’ rights ‘to rule the state’ that will ensure the existence of current and future generations.